Sigma‐2 receptor antagonists rescue neuronal dysfunction induced by Parkinson's patient brain‐derived α‐synuclein. Issue 4 (22nd January 2021) - Limegrover, Colleen S.; Yurko, Raymond; Izzo, Nicholas J.; LaBarbera, Kelsie M.; Rehak, Courtney; Look, Gary; Rishton, Gilbert; Safferstein, Hank; Catalano, Susan M.
Abstract: α‐Synuclein oligomers are thought to have a pivotal role in sporadic and familial Parkinson's disease (PD) and related α‐synucleinopathies, causing dysregulation of protein trafficking, autophagy/lysosomal function, and protein clearance, as well as synaptic function impairment underlying motor and cognitive symptoms of PD. Moreover, trans‐synaptic spread of α‐synuclein oligomers is hypothesized to mediate disease progression. Therapeutic approaches that effectively block α‐synuclein oligomer‐induced pathogenesis are urgently needed. Here, we show for the first time that α‐synuclein species isolated from human PD patient brain and recombinant α‐synuclein oligomers caused similar deficits in lipid vesicle trafficking rates in cultured rat neurons and glia, while α‐synuclein species isolated from non‐PD human control brain samples did not. Recombinant α‐synuclein oligomers also increased neuronal expression of lysosomal‐associated membrane protein‐2A (LAMP‐2A), the lysosomal receptor that has a critical role in chaperone‐mediated autophagy. Unbiased screening of several small molecule libraries (including the NIH Clinical Collection) identified sigma‐2 receptor antagonists as the most effective at blocking α‐synuclein oligomer‐induced trafficking deficits and LAMP‐2A upregulation in a dose‐dependent manner. These results indicate that antagonists of the sigma‐2 receptor complex may alleviate α‐synuclein oligomer‐induced neurotoxicity and are a novel therapeutic approach for disease modification in PD and related α‐synucleinopathies. Abstract : The protein α‐synuclein is central to Parkinson's disease. For the first time, we report that α‐synuclein from Parkinson's patients brain samples caused signaling deficits in brain cells, and novel drug candidates known to block the sigma‐2 receptor complex reversed these deficits.